Understanding the impact of the central atom on the ionic liquid behavior: Phosphonium vs ammonium cations - Carvalho, Pedro J. (2017)
The influence of the cation's central atom in the behavior of pairs of ammonium- and phosphonium-based ionic liquids was investigated through the measurement of densities, viscosities, melting temperatures, activity coefficients at infinite dilution, refractive indices, and toxicity against Vibrio fischeri. All the properties investigated are affected by the cation's central atom nature, with ammonium-based ionic liquids presenting higher densities, viscosities, melting temperatures, and enthalpies. Activity coefficients at infinite dilution show the ammonium-based ionic liquids to present slightly higher infinite dilution activity coefficients for non-polar solvents, becoming slightly lower for polar solvents, suggesting that the ammonium-based ionic liquids present somewhat higher polarities. In good agreement these compounds present lower toxicities than the phosphonium congeners. To explain this behavior quantum chemical gas phase DFT calculations were performed on isolated ion pairs at the BP-TZVP level of theory. Electronic density results were used to derive electrostatic potentials of the identified minimum conformers. Electrostatic potential-derived CHelpG and Natural Population Analysis charges show the P atom of the tetraalkylphosphonium-based ionic liquids cation to be more positively charged than the N atom in the tetraalkylammonium-based analogous IL cation, and a noticeable charge delocalization occurring in the tetraalkylammonium cation, when compared with the respective phosphonium congener. It is argued that this charge delocalization is responsible for the enhanced polarity observed on the ammonium based ionic liquids explaining the changes in the thermophysical properties observed. (C) 2014 AIP Publishing LLC.